Comparison of Cornell sprinkle infiltrometer and double‐ring infiltrometer methods for measuring steady infiltration rate. Issue 6 (14th September 2021) - Lewis, John; Amoozegar, Aziz; McLaughlin, Richard A.; Heitman, Joshua L.
Abstract: Infiltration rate measurements are used to assess soil health and develop land management practices to address runoff from precipitation and irrigation. Differences in observed infiltration rates determined by available methods can be attributed to both the technique and soil property differences. The primary objective of this study was to compare two methods for measuring steady infiltration rate: the Cornell sprinkle infiltrometer (single‐ring) method (CSI), and the double‐ring infiltrometer method (DRI). Measurements were made at four sites using four replications of 13 sets of conditions (52 total paired measurements). The relationship between CSI and DRI measurements was significant ( p  < .001) and strong ( R 2  = .71). For 8 of 13 conditions, there was no difference between CSI and DRI steady infiltration rates. Variability in measurements was high (CVs ranged from 0.04 to 1.18) but similar for both methods. Both CSI and DRI results were strongly related to saturated hydraulic conductivity of the surface soil layer determined using a laboratory constant head method on intact soil cores. Overall, results suggest that estimates of steady infiltration rate determined by the CSI and standard DRI methods are comparable. Core Ideas: Cornell sprinkle and double‐ring infiltrometer measurements were compared. Results for the methods were strongly related and similar over a range of conditions. Both methods had large variability in replicate infiltration measurements. Infiltration rates were strongly related to surface saturated hydraulic conductivity.